Transformasi Digital Pengawasan Pendidikan: Strategi Mengatasi Ketimpangan Rasio Pengawas Madrasah di Provinsi Jambi - Anwar (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article is motivated by a serious challenge in madrasah (Islamic school) supervision in Jambi Province: the extreme disparity in the supervisor-to-madrasah (Islamic school) ratio, which leads to ineffective supervision and widens the quality gap between regions. Data shows a sharp disparity, from the ideal ratio of 1:4.4 in Jambi City to an excessive workload of 1:25.5 in West Tanjung Jabung Regency, which reduces supervision to an administrative formality and compromises its pedagogical development function. Through USG analysis, the issue of